RESULTS REGARDING THE EFFECT OF VARIOUS FACTORS ON THE MAIN QUANTITATIVE AND QUALITATIVE TRAITS OF MILK TO A POPULATION OF ROMANIAN COW BREED - CAMELIA RĂDUCU; VIOARA MIREŞAN; AURELIA PECE; C. COROIAN; DANA PUSTA; O. NEGREA (Scientific Papers Animal Science and Biotechnologies, 2023)
The study intends to be a further of a more complex one, as regards on the main quantitative and qualitative traits of milk to a romanian population of cow, which is exploited mainly in the central region of Romania.